2006
DOI: 10.1542/peds.2005-2931
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features Affecting Final Adult Height in Patients With Pediatric-Onset Crohn's Disease

Abstract: Mean final adult height showed a modest deficit compared with target height, but in one fifth of patients, final height was significantly less than target height. Earlier diagnosis and improved treatment of jejunal disease would be likely to improve final height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
154
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 28 publications
10
154
1
4
Order By: Relevance
“…One of the most important risk factors for reduced height during the course of disease is the time from symptom onset to diagnosis [13]. Proximal small bowel disease location in children with CD was also implicated as a contributing factor to growth delay [14,15], possibly attributed to increased burden of systemic inflammation and malabsorption of micronutrients. Growth impairment in pediatric CD patients was also associated with positivity of ASCA antibodies [16].…”
Section: Definition and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important risk factors for reduced height during the course of disease is the time from symptom onset to diagnosis [13]. Proximal small bowel disease location in children with CD was also implicated as a contributing factor to growth delay [14,15], possibly attributed to increased burden of systemic inflammation and malabsorption of micronutrients. Growth impairment in pediatric CD patients was also associated with positivity of ASCA antibodies [16].…”
Section: Definition and Prevalencementioning
confidence: 99%
“…Kanof et al [6] have demonstrated that 46% of children with CD will have a reduced height velocity before the appearance of suggestive symptoms and only 12% continue to follow normal growth patterns at the time of diagnosis while Malik et al [12] reported that the percentage of children with height velocity SDS between −1 and −2 was 49% at diagnosis. Unfortunately, the natural course of CD results in decreased adult height in 11-35% of pediatric patients [8,14,21]. Furthermore, growth impairment in children with CD was found to be a predictor for more disabling disease [22].…”
Section: Definition and Prevalencementioning
confidence: 99%
“…It is of interest in this context that different clinical phenotypes are seen, including short underweight, short normal-weight and normal-height underweight. There are many factors that contribute to this feature, including timing of the onset of disease related to puberty, timing of puberty and expected height when parental heights are considered together with the contribution of nutritional intake, nutritional status, the inflammatory response, endocrine factors and the disease management (8) . The delay in growth is linear in that both growth and puberty and therefore physical maturity are delayed.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…The striking impact of this in a proportion of cases is that the child looks younger than their chronological age and therefore may be treated as such, with all the consequent psychological sequelae added to the impact of coping with a chronic disease during adolescence. The second important impact of this growth delay is that it is not uncommon for young patients with Crohn's disease to continue to grow into their late teens, when most adolescents have completed their growth, with continued improvement after age 16 years, as evidenced by continued improvement in height SD score in long-term follow-up data (8) . It is important in the young patient in the adult clinic to be aware of where there may still be potential for growth, particularly if puberty is not complete, and clinical assessment should include careful documentation of weight, height, height velocity and pubertal status.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…demonstraram prognóstico favorável do crescimento durante o período de crescimento até atingir a altura adulta. Aproximadamente 20% dos pacientes ficaram com altura final mais de 8 cm abaixo do alvo familiar, sendo mais comprometidos aqueles que já apresentavam baixa estatura no diagnóstico da doença e aqueles com comprometimento de jejuno (41). A suplementação nutricional adequada e a ressecção cirúrgi-ca da porção intestinal acometida levam à melhora do crescimento, porém alguns pacientes não conseguem recuperar totalmente o crescimento (42).…”
Section: Doença De Crohnunclassified